Mortality in elderly patients admitted for respite care. Issue 6728 (31st March 1990) - Howarth, S; Clarke, C; Bayliss, R; Whitfield, A G; Semmence, J; Healy, M J
Abstract : OBJECTIVE--To determine whether admitting elderly patients to hospital to give temporary relief to their carers is associated with increased mortality. DESIGN--Prospective multicentre study comparing the mortality of patients admitted on a one off or rotational basis with that experienced while they were awaiting admission. SETTING--A wide range of urban and rural district general, geriatric or long stay, and general practitioner hospitals. PATIENTS--474 Patients aged 70 or over who had 601 admissions. MAIN OUTCOME MEASURE--Death. RESULTS--16 (3.4%) Of the 474 patients (2.7% of all 601 admissions) died while in hospital during an average stay of 15.7 days whereas 23 (4.9%) patients died while awaiting admission (average waiting time was 34.2 days). The 16 deaths in hospital and the 23 deaths during the longer waiting period correspond to death rates of 19.9 and 12.5 per 10, 000 person days respectively. The difference between these of 7.4 is not statistically significant (95% confidence interval -3.6 to 18.3). The estimated relative risk of dying in hospital is 1.59 but the 95% confidence interval is wide (0.84 to 3.01). CONCLUSION--Although the death rates are slightly higher in those admitted to hospital for relief care than in those awaiting admission, the difference was not significant, and the death rate in both groups was reassuringly small.